LEGAL PROTECTION FOR VICTIMS WRONGLY ARRESTED IN THE INVESTIGATION PROCESS IN INDONESIA - Burhayan; Mujiburrahman (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study discusses legal protection for victims of wrongful arrest during the investigation process in Indonesia. As a state governed by law, Indonesia guarantees the protection of human rights, including for those who become victims of procedural errors in the justice system. Wrongful arrests constitute a violation of individual freedom and cause physical, psychological, and social suffering. This research employs a normative legal method, drawing on statutory and literature sources. The results show that victims of wrongful arrest are entitled to compensation and rehabilitation, as provided for in the Indonesian Criminal Procedure Code (KUHAP) and Law Number 48 of 2009 concerning Judicial Power. However, compensation provided is still limited to material aspects and has not fully restored the victims’ dignity, reputation, and well-being. Therefore, the state must strengthen legal protection mechanisms and ensure that investigations are conducted professionally, transparently, and in accordance with human rights principles to prevent the recurrence of wrongful arrest cases.